THE PSYCHOLOGICAL CONTENT OF PROVOKING PROVOKING IN ADOLESCENTS - Axmatova Guli Xurram qizi (The Conference Hub, 2025)
This article explores the psychological aspects of negative changes that occur in adolescence. Adolescence is one of the most important stages of a person's life, during which social, emotional, and physiological changes are manifested at a high level.The article analyzed the causes of negative states such as stress, anxiety, and depression and the impact on adolescents' personal development. Effective psychological approaches to overcoming such problems were also considered.
Keywords: adolescence, social environment, developmental crisis, psychological changes, stress, emotional balance, anxiety, depression, personal development, psychological approaches, problem-solving, negative influences, adaptation process